IMPLEMENTASI KEBIJAKAN PENGADAAN BARANG/ JASA PEMERINTAH TENTANG PROGRAM BELA PENGADAAN - Ellen Meilinda Nainggolan; Siti Mardiana; Adam Adam (Universitas Bina Taruna Gorontalo, 2023)
TThe purpose of this study was to examine the implementation of the policy of the decision at the regional office of the BPN, North Sumatra Province through George Edward III's theory of policy implementation, and to examine the inhibiting factors in implementing the policy. The method used is descriptive qualitative, using data collection techniques through interviews, observations and documentation studies. The data analysis technique uses the Miles, Huberman Saldana interactive model with the stages of data collection, data reduction, data presentation, and drawing conclusions. The results of the study found that the Procurement of Bela program at the BPN Regional Office of North Sumatra Province had been carried out well, and it could be said that the procurement officials had succeeded. This can be seen from the communication factor that exists between procurement officials and other stakeholders. The existence of competent human resources and adequate infrastructure resources. There is an attitude of implementers who are highly committed in carrying out their duties, and the activities of procuring goods and services are in accordance with the procedures or procedures drawn up by LKPP. However, there are still obstacles related to the lack of provider participation in the procurement of Bela platform, resulting in a lack of product choices. In addition, there are still obstacles in ordering consumption for the sake of meeting or large events, especially those that are carried out impromptu.